2018
DOI: 10.1111/lang.12327
|View full text |Cite
|
Sign up to set email alerts
|

Primed From the Start: Syntactic Priming During the First Days of Language Learning

Abstract: New linguistic information must be integrated into our existing language system. Using a novel experimental task that incorporates a syntactic priming paradigm into artificial language learning, we investigated how new grammatical regularities and words are learned. This innovation allowed us to control the language input the learner received, while the syntactic priming paradigm provided insight into the nature of the underlying syntactic processing machinery. The results of the present study pointed to facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…Furthermore, an AL learning study by Wonnacott, Newport and Tanenhaus (2008) showed that learners produce frequent structures in the AL more often than less frequent ones, which suggests that the probabilistic structure of the AL was reflected in the learners' AL productions. In contrast, a recent study investigating structural priming in comprehension during AL learning by Weber et al (2019) did not find any effect of the frequency of word orders in the AL.…”
Section: The Role Of Frequencycontrasting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, an AL learning study by Wonnacott, Newport and Tanenhaus (2008) showed that learners produce frequent structures in the AL more often than less frequent ones, which suggests that the probabilistic structure of the AL was reflected in the learners' AL productions. In contrast, a recent study investigating structural priming in comprehension during AL learning by Weber et al (2019) did not find any effect of the frequency of word orders in the AL.…”
Section: The Role Of Frequencycontrasting
confidence: 84%
“…This suggests that abstract syntactic representations are mainly present in high-proficient speakers. Another line of evidence stems from a series of studies that investigated structural priming in an artificial language (AL) learning paradigm (Muylle, Bernolet, & Hartsuiker, 2020, 2021, in press; Weber, Christiansen, Indefrey, & Hagoort, 2019), that allows to study the development of shared syntactic representations in very early stages of L2 acquisition. In a multiple session version of this paradigm, Muylle and colleagues (2021) found evidence for a gradual development of shared syntactic representations in ditransitives (i.e., DO datives and prepositional-object datives, henceforth PO), given that cross-linguistic priming only reliably emerged from the second day of training (in contrast to transitives, which showed cross-linguistic priming already on the first day).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the motivation of a participant to study a non-existing language might be different from people studying a natural language, that serves a communicative purpose in life. Despite these limitations, AL learning paradigms have proven to be a promising tool in second language acquisition research (e.g., Muylle et al, submitted;Weber, Christiansen, Indefrey, & Hagoort, 2019;Wonnacott et al, 2008) and seem to replicate processes and phenomena that are also observed in natural language learning situations. For instance, Muylle and colleagues (submitted) studied structural priming in a five session AL learning design and found priming within the AL during all sessions, and a lexical boost effect, comparable to what has been found in natural language experiments.…”
Section: The Artificial Language Learning Paradigmmentioning
confidence: 99%
“…The magnitude of these effects tends to be greater for less frequent structures (known as inverse probability effects). This has been observed empirically in both the L1 and L2: Structures that have lower frequency in the input elicit greater priming effects (Hartsuiker et al, 1999;Hartsuiker & Westenberg, 2000;Jaeger & Snider, 2013;Kaan & Chun, 2018b;Kaschak, 2007;Kaschak et al, 2006;Montero-Melis & Jaeger, 2019;Weber et al, 2019).…”
Section: Structural Priming As a Learning Mechanismmentioning
confidence: 60%